Job Satisfaction as a Mediator of the Effect of Work Motivation and Work Environment on Employee Performance - Berlianto, Christopel; Rahmawati, Putu Indah; Heryanda, Komang Krisna (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study investigates the influence of work motivation and work environment on employee performance, with job satisfaction serving as a mediating variable at PT Kona Bay Indonesia, a global aquaculture breeding enterprise. The research employs a quantitative approach using primary data collected through structured questionnaires distributed to employees. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4 software to test both direct and indirect relationships among variables. The results reveal that work motivation and work environment each have positive and significant effects on job satisfaction and employee performance. Furthermore, job satisfaction has a strong and significant impact on employee performance, acting as a partial mediator between the independent variables and the dependent variable. The mediation test using the Variance Accounted For (VAF) method shows that job satisfaction explains 39.51% of the effect of work motivation on performance and 41.14% of the effect of work environment on performance, confirming partial mediation in both relationships. These findings highlight that motivated employees who operate in a supportive work environment tend to experience higher job satisfaction, which subsequently enhances their productivity and overall performance. The study contributes theoretically by validating the mediating role of job satisfaction and practically by emphasizing the importance of motivational programs and workplace improvements to strengthen employee engagement and performance.